2020
DOI: 10.1364/ao.406190
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of iris elasticity using acoustic radiation force optical coherence elastography

Abstract: Careful quantification of the changes in biomechanical properties of the iris can offer insight into the pathophysiology of some ocular diseases. However, to date there has not been much information available regarding this subject because clinical detection for iris elasticity remains challenging. To overcome this limitation, we explore, for the first time to our knowledge, the potential of measuring iris elasticity using acoustic radiation force optical coherence elastography (ARF-OCE). The resulting images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…The method employed was indirect and thus, is unsuitable for obtaining the absolute value of the elastic modulus. Zhu et al [37] evaluated the elasticity of the rabbit iris using ARF OCE. The excitation system they used contained an ultrasound transducer, which still required contact with the eyeball to generate shear waves within the iris.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The method employed was indirect and thus, is unsuitable for obtaining the absolute value of the elastic modulus. Zhu et al [37] evaluated the elasticity of the rabbit iris using ARF OCE. The excitation system they used contained an ultrasound transducer, which still required contact with the eyeball to generate shear waves within the iris.…”
Section: Discussionmentioning
confidence: 99%
“…where E is Young's modulus, v is Poisson's ratio (because the iris is considered an incompressible material under small strains, v = 0.49), and ρ is the density of the iris (ρ = 1250 kg/m 3 according to the literature [22,37]).…”
Section: Oce Data Acquisition and Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to abnormal morphological changes, the iris also undergoes natural variations due to its function in the eye (contraction and expansion) [11]. Several studies have shown interest in determining the biomechanical properties of the iris, under different conditions (in vivo or ex vivo) using animal models [12][13][14] or human volunteers [11], using different techniques such as Atomic Force Microscopy (AFM) [15], Optical Coherence Tomography (OCT) [9], and Optical Coherence Elastography (OCE) [11,14,16]. Although AFM showed a high capacity to determine the stiffness of the iris, it had several limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, OCE is rapidly gaining popularity for assessing tissue biomechanical properties [22,23]. OCE can describe the biomechanical differences among the different tissues of the same organs, such as the detailed description of the biomechanical properties of the inner structure of the eye [20,[24][25][26], including the iris [11,16]. However, these studies have not investigated the effects of intraocular pressure (IOP) changes on the stiffness of the iris.…”
Section: Introductionmentioning
confidence: 99%